Platinum-Free Counter Electrode Comprised of Metal-Organic-Framework (MOF)-Derived Cobalt Sulfide Nanoparticles for Efficient Dye-Sensitized Solar Cells (DSSCs) - Hsu, Shao-Hui; Li, Chun-Ting; Chien, Heng-Ta; Salunkhe, Rahul R.; Suzuki, Norihiro; Yamauchi, Yusuke; Ho, Kuo-Chuan; Wu, Kevin C.-W. (Scientific reports, 2014)
We fabricated a highly efficient (with a solar-to-electricity conversion efficiency (η) of 8.1%) Pt-free dye-sensitized solar cell (DSSC). The counter electrode was made of cobalt sulfide (CoS) nanoparticles synthesized via surfactant-assisted preparation of a metal organic framework, ZIF-67, with controllable particle sizes (50 to 320 nm) and subsequent oxidation and sulfide conversion. In contrast to conventional Pt counter electrodes, the synthesized CoS nanoparticles exhibited higher external surface areas and roughness factors, as evidenced by X-ray diffraction (XRD), scanning electron microscopy (SEM) element mapping and electrochemical analysis. Incident photon-to-current conversion efficiency (IPCE) results showed an increase in the open circuit voltage (V OC ) and a decrease in the short-circuit photocurrent density (Jsc) for CoS-based DSSCs compared to Pt-based DSSCs, resulting in a similar power conversion efficiency. The CoS-based DSSC fabricated in the study show great potential for economically friendly production of Pt-free DSSCs.